Acute effects of passive static tretching during warm-up on driver clubhead speed, distance, accuracy, and consistent ball contact in young male competitive golfers - Gergley, J. C. (The Journal of Strength and Conditioning Research, 2009)
This investigation was conducted to determine the effect of 2 different warm-up treatments on clubhead speed, distance, accuracy, and consistent ball contact in 15 young male competitive golfers. Two supervised warm-up treatments, an active dynamic warm-up with golf clubs (AD) and a 20-minute total-body passive static stretching routine plus an identical AD warm-up (SS), were applied before each performance testing session using a counterbalanced design on nonconsecutive days. Immediately after each warm-up treatment, subjects were instructed to hit 10 full-swing golf shots with their driver after their normal preshot routine, with 1 minute of rest between trials. Significant (p < 0.05) decreases in clubhead speed (-4.19%), distance (-5.62%), accuracy (-31.04%), and consistent ball contact (-16.34%) were observed. Theoretical explanations for this acute decrease in performance include a more compliant muscle tendon unit, decreased neuromuscular reflex sensitivity, and neural inhibition attributable to the SS treatment. The results of this inquiry strongly suggest that a total-body passive static stretching routine should be avoided before practice or competition in favor of a gradual, active dynamic with golf clubs.